Disease Resistance Genetics and Genomics in Octoploid Strawberry. Issue 10 (1st October 2019) - Barbey, Christopher R; Lee, Seonghee; Verma, Sujeet; Bird, Kevin A; Yocca, Alan E; Edger, Patrick P; Knapp, Steven J; Whitaker, Vance M; Folta, Kevin M
Abstract: Octoploid strawberry ( Fragaria ×ananassa ) is a valuable specialty crop, but profitable production and availability are threatened by many pathogens. Efforts to identify and introgress useful disease resistance genes (R-genes) in breeding programs are complicated by strawberry's complex octoploid genome. Recently-developed resources in strawberry, including a complete octoploid reference genome and high-resolution octoploid genotyping, enable new analyses in strawberry disease resistance genetics. This study characterizes the complete R-gene collection in the genomes of commercial octoploid strawberry and two diploid ancestral relatives, and introduces several new technological and data resources for strawberry disease resistance research. These include octoploid R-gene transcription profiling, d N/ d S analysis, expression quantitative trait loci (eQTL) analysis and RenSeq analysis in cultivars. Octoploid fruit eQTL were identified for 76 putative R-genes. R-genes from the ancestral diploids Fragaria vesca and Fragaria iinumae were compared, revealing differential inheritance and retention of various octoploid R-gene subtypes. The mode and magnitude of natural selection of individual F. ×ananassa R-genes was also determined via d N/ d S analysis. R-gene sequencing using enriched libraries (RenSeq) has been used recently for R-gene discovery in many crops, however this technique somewhat relies upon a priori knowledge of desired sequences. An octoploid strawberry capture-probe panel, derived from the results of this study, is validated in a RenSeq experiment and is presented for community use. These results give unprecedented insight into crop disease resistance genetics, and represent an advance toward exploiting variation for strawberry cultivar improvement.